2022
DOI: 10.3389/fcimb.2022.846063
|View full text |Cite
|
Sign up to set email alerts
|

More Positive or More Negative? Metagenomic Analysis Reveals Roles of Virome in Human Disease-Related Gut Microbiome

Abstract: Viruses are increasingly viewed as vital components of the human gut microbiota, while their roles in health and diseases remain incompletely understood. Here, we first sequenced and analyzed the 37 metagenomic and 18 host metabolomic samples related to irritable bowel syndrome (IBS) and found that some shifted viruses between IBS and controls covaried with shifted bacteria and metabolites. Especially, phages that infect beneficial lactic acid bacteria depleted in IBS covaried with their hosts. We also retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…A recent study on CRC studied the relevance of the interplay between viruses and bacteria, highlighting the importance of the co‐occurrence of bacteriophages and their influence on the bacterial communities. 39 The present study identified four different phages: all of them were identified while performing metagenomics ( Acionnavirus Synechococcus phage S‐CAM8 [closely related to Synechococcus phage s rim8 , known to be enriched in late CRC stages 40 ], Eganvirus Salmonella phage SW9, Aeribacillus phage AP45 , and uncultured crAssphage ) and only one of them was detected when analyzing metatrascriptomics ( Aeribacillus phage AP45 ). While 3/4 phages detected in metagenomics showed an increased relative abundance in CRC, as reported by other authors, 41 , 42 the present study did not find any statistical significance.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A recent study on CRC studied the relevance of the interplay between viruses and bacteria, highlighting the importance of the co‐occurrence of bacteriophages and their influence on the bacterial communities. 39 The present study identified four different phages: all of them were identified while performing metagenomics ( Acionnavirus Synechococcus phage S‐CAM8 [closely related to Synechococcus phage s rim8 , known to be enriched in late CRC stages 40 ], Eganvirus Salmonella phage SW9, Aeribacillus phage AP45 , and uncultured crAssphage ) and only one of them was detected when analyzing metatrascriptomics ( Aeribacillus phage AP45 ). While 3/4 phages detected in metagenomics showed an increased relative abundance in CRC, as reported by other authors, 41 , 42 the present study did not find any statistical significance.…”
Section: Discussionmentioning
confidence: 86%
“…Regarding viruses, there were no viral species detected as statistically significant in any of the groups (tumors vs mucosa) despite the depth of sequencing achieved. A recent study on CRC studied the relevance of the interplay between viruses and bacteria, highlighting the importance of the co‐occurrence of bacteriophages and their influence on the bacterial communities 39 . The present study identified four different phages: all of them were identified while performing metagenomics ( Acionnavirus Synechococcus phage S‐CAM8 [closely related to Synechococcus phage s rim8 , known to be enriched in late CRC stages 40 ], Eganvirus Salmonella phage SW9, Aeribacillus phage AP45 , and uncultured crAssphage ) and only one of them was detected when analyzing metatrascriptomics ( Aeribacillus phage AP45 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lactobacillus virus LBR4 8, a phage that infects Lactobacillus brevis , commonly considered a probiotic, was increased in IBS-C patients, possibly interfering with L. brevis activity. 85 …”
Section: Virome Databasesmentioning
confidence: 99%
“…The authors demonstrate that their novel neural architecture performs better than other available methods. Specifically, they compared the performance of Jaeger to PPRMeta, DeepVirFinder, Seeker, and VirSorter2 on the phages in the IMGVR (v4) database and real metagenomic datasets from three different biomes, showing 10–35% decrease in false positive rate without compromising on sensitivity [ 10 , 11 , 12 , 13 , 14 , 15 ]. Together, Jaeger adds a new AI-powered tool to the metagenomics toolbox that will help to understand the composition of complex communities from metagenomic sequencing.…”
Section: Scientific Programmentioning
confidence: 99%